The largest aluminum molecular rings: Phenol‐thermal synthesis, photoluminescence, and optical limiting - San‐Tai Wang; Ya‐Jie Liu; Cheng‐Cheng Feng; Wei‐Hui Fang; Jian Zhang (Aggregate, 2023)
Abstract It is of great interest to modulate the photophysical properties by atomically precise chemical control. The incorporation of conjugated ligands into crystalline materials provides a platform for molecular‐level interpretation of the structure‐activity relationship. Herein, we reported the phenol‐thermal and scale‐up synthesis of a new family of remarkably stable aluminum molecular rings. They are assembled by twenty AlIII ions with large conjugated ligands and phenols, representing the currently largest sizes (up to 4 nm in diameter) in the field of main group metal oxo clusters. Phenols are not only reaction medium but also auxiliary bridging ligands on the surface of macrocyclic molecules. In addition, they are either parallel to the center of the molecular ring or inserted into the molecular ring, or form dimers/tetramers that bind macrocyclic molecules to form supramolecular structures. These macrocyclic rings are hydrophobic and ultra‐stable, evidenced by retaining their morphology and crystalline when exposed to air for more than a year. Compared with the pristine conjugated ligands, they exhibit coordination‐enhanced fluorescence. By dispersing them into a polydimethylsiloxane (PDMS) matrix, we prepared transparent and flexible PDMS thin films for coupling flexible display and nonlinear optical application. Our discovery of such atomically precise rings provides a platform for the fine‐tuning of photo‐related performances.